Online Learning in Secondary Education: A New Frontier - Simone Conceição; Sarah B. Drummond (Educational Considerations, 2005)
Distance education is not a new concept in the educational arena. In 1892, it was established in the United States with correspondence study at the University of Chicago through the home study department of the Division of Extension.